Effects of temperature on growth and survival of laboratory-reared larvae of the scaled sardine, harengula pensacolae goode and bean - Saksena, Vishnu P; Steinmetz, Charles; Houde, Edward D (Transactions of The American Fisheries Society, 1972)
Growth and survival of scaled sardine, Harengula pensacolae, larvae were evaluated in laboratory rearing experiments at temperatures ranging from 21 to 35 C. Fertilized eggs were obtained in plankton collections made near Miami, Florida, in summer 1971. Larvae were reared for 15 days after hatching in temperature-controlled, 75-liter aquaria. Hatching success was high at all temperatures but larvae did not survive at 35 C, and survival was poor at 21-23 C. Survival was best at temperatures between 26 and 32 C. Mean daily growth increments ranged from 0.056 mm at 21-23 C to 1.035 mm at 32 C. Growth in relation to temperature was expressed by the equation Y = -0.8474 + 0.0537X, where Y equals daily growth increment and X equals temperature. Larval behavior was normal at 26 to 33.5 C. Critical high and low temperatures for larval survival were 35 C and approximately 20 C. © 1972 by the American Fisheries Society.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/152-113-400-823-245 tex.type: [object Object]
Keywords: dept.bio